Metastatic colon adenocarcinoma presenting as a giant inguinal hernia: A case report. (April 2023) - Hebert, Danielle; Sripathi, Shravani; Versluis, Eric; Hackett, Timothy; Solh, Wael
Abstract: Introduction and importance: Giant inguinoscrotal hernias (GIH) are a rare form of inguinal hernia. There have been few reported cases of GIH containing colon adenocarcinoma. Case presentation: This case describes a 72-year-old male with a right GIH containing the right colon, terminal ileum, and associated mesentery with a large heterogenous, irregular mass with necrosis involving the cecum and ascending colon measuring 14 × 8 × 9 cm. The patient initially presented with pain and evidence of partial large bowel obstruction. Due to suspected extensive local invasion of tumor, the patient was scheduled for evaluation for possible neoadjuvant chemotherapy. Unfortunately, the patient re-presented with a large bowel obstruction and was subsequently taken for an exploratory laparotomy with trans-scrotal incision for en bloc resection of cecal adenocarcinoma and involved hernia contents. Clinical discussion: Due to the rarity of this pathology, there is not a standard approach to management or optimal surgical technique described. In this case, a trans-scrotal incision paired with an exploratory laparotomy allowed for superior access to the adhered cancer containing bowel as well as skin excision, following standard oncologic principle of high ileocolic mesenteric excision. Conclusion: The complexity of management of GIH containing colon cancer has been documented, however a standard oncologic approach has not been described. This case report presents exploratory laparotomy with trans-scrotal incision as an approach. Highlights: Giant inguinoscrotal hernias containing colon cancer are rare. Treatment of colon cancer within inguinal hernias may be approached via two-incisions. There is no standard surgical approach for cancer containing inguinal hernias.